(untitled) (Research, Society and Development, 2022)
Hysterectomy is a gynecological surgical procedure that consists of removing the uterus, being one of the most frequent surgeries in women. It is the second surgey perfomed in the female population of childbearing age, after cesarean.The aim of the study was to investigate the epidemiological profile and factors that may be associated with hysterectomized women treated at the Francisco Beltrão’s Cancer Hospital. This is an observational and cross-sectional study where 113 women who underwent routine gynecological examination at the Francisco Beltrão’s Cancer Hospital in 2019 were recruited by the convenience method. In the results, some possible factors associated with hysterectomy were observed: women with age over 45 years, income of at least two minimum wages, non-hypertensive, with marital status or stable union, users of oral contraceptives and who underwent gynecological examination in a time interval of at least two years had a lower chance of having been hysterectomized.